2014
DOI: 10.3390/ijms151120240
|View full text |Cite
|
Sign up to set email alerts
|

Pressure Overload-Induced Cardiac Hypertrophy Response Requires Janus Kinase 2-Histone Deacetylase 2 Signaling

Abstract: Pressure overload induces cardiac hypertrophy through activation of Janus kinase 2 (Jak2), however, the underlying mechanisms remain largely unknown. In the current study, we tested whether histone deacetylase 2 (HDAC2) was involved in the process. We found that angiotensin II (Ang-II)-induced re-expression of fetal genes (Atrial natriuretic peptide (ANP) and brain natriuretic peptide (BNP)) in cultured cardiomyocytes was prevented by the Jak2 inhibitor AG-490 and HDAC2 inhibitor Trichostatin-A (TSA), or by Ja… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 31 publications
(32 reference statements)
0
4
0
Order By: Relevance
“…Angiotensin II (Ang II), a potent stimulus of cardiac myocyte growth factors, has been found to be elevated in cardiac failure ( Zucker et al, 2015 ). Ang II can be used to mimic pressure-overload-induced cardiac hypertrophy ( Ying et al, 2014 ) and has been widely employed as a hypertrophic stimulus in various in vitro cardiac disease models ( Ding et al, 2019 ).…”
Section: Introductionmentioning
confidence: 99%
“…Angiotensin II (Ang II), a potent stimulus of cardiac myocyte growth factors, has been found to be elevated in cardiac failure ( Zucker et al, 2015 ). Ang II can be used to mimic pressure-overload-induced cardiac hypertrophy ( Ying et al, 2014 ) and has been widely employed as a hypertrophic stimulus in various in vitro cardiac disease models ( Ding et al, 2019 ).…”
Section: Introductionmentioning
confidence: 99%
“…The beneficial effects of metformin on cardiac function have been attributed to direct actions on cell metabolism, endothelial function, platelet reactivity and calcium homeostasis (25). Since hypertrophic stimuli, including angiotensin II and pressure overload, may increase the expression of ANP and BNP (26), the mRNA levels of ANP and BNP following metformin and/or Ang II treatment were investigated as hypertrophic markers in the present study. The results revealed that metformin significantly suppressed the development of Ang II-induced cardiomyocyte hypertrophy as evidenced by reductions in cardiomyocyte surface area, reduced expression of hypertrophy-associated genes ANP and BNP in Ang II-stimulated cardiomyocytes.…”
Section: Discussionmentioning
confidence: 99%
“…In parallel with highlighting the anti-apoptotic/anabolic pro le of the cardiac myotubes in response to different loading conditions, this study also examined the expression responses of pro-apoptotic and muscle atrophy genes to the various mechanical stimuli. While many studies have suggested potentially bene cial effects of mechanical stretching on cardiomyocytes structure and function [1,[44][45][46], nevertheless, excessive mechanical stimuli have been reported to induce cardiac cell apoptosis and maladaptive hypertrophy, which promote upregulation of atrophy and in ammation factors [7,36,47].…”
Section: Discussionmentioning
confidence: 99%